Perancangan Aplikasi Sistem Informasi Akuntansi Persediaan Dengan Menggunakan Microsoft Access 2019: (Studi Kasus pada UMKM Toko Syarifah-Rancaekek) - Putri, Salwa Ananda; Hutapea, Riauli Susilawaty (Indonesian Accounting Literacy Journal, 2025)
All companies in various fields need a good information system so that their business operations can run effectively and efficiently. In this increasingly modern era, technology has become an important part of human life, one of which is in the company’s business operations. In the application of information systems in a company, technology is increasingly providing convenience and benefits in the work process – Syarifah Store is a small-scale trading company that also has a convection industry to produce Muslim clothing for adult women herself. In business activities, Syarifah Store currently still uses manual recording, one of which is inventory recording activities that still use paper. This manual inventory recording system is considered impractical and the resulting information is not always accurate and precise. The researcher aims to design a finished goods inventory application program at the Syarifah Store. The method used in this design is the SDLC (System Development Life Cycle) method. This application is made to record inventory movements of finished goods, determine the cost of goods sold using the moving average method, present reports of incoming and outgoing finished goods, and present inventory stock reports. The design of this application uses the Microsoft Access 2019 database.